Oil flowers of Malpighiaceae and its oil-collecting bees: loyalty and robbery in a highly specialized system - Torretta, Juan Pablo (2022)
Plant-pollinator interactions are generally mutualistic, but if one of the partners can get rewards without providing any services in return, these interactions become antagonistic. In the oil flower syndrome, the highly specialized system suggests a high degree mutualism; however, there are reports of illegitimate oil-collecting bees in flowers of Malpighiaceae. We evaluated the legitimate and illegitimate visits to flowers in 15 species of this plant family along a latitudinal gradient in Argentina. Our results show that oil robbery in most of the Malpighiaceae analyzed species was as common as the legitimate collection of this resource by oil-collecting bees, and significant differences in the proportion of illegitimate visits along the latitudinal gradient, being the robbery more common to southern sites.